Morality at play. (3rd December 2018) - Bateman, Amanda; Roberts, Peri
Abstract : The concept of 'play' is notoriously ambiguous, but we do know that when children engage in make-believe play the activity provides benefits for psychological development, holistic health, and building knowledge and relationships. This article discusses how a group of four-year-old children in New Zealand engage in pretend play by embodying the characters of mud-monsters and possums to avoid the rules around being respectful to their cultural heritage while playing in a protected bush reserve. The data were generated through a project investigating teaching and learning in everyday conversations between preschool teachers and children aged 2½-5 years old. Ten hours of video footage were gathered, of which one hour and forty minutes were in rural bushland. The analysis of the footage here uses an ethnomethodological framework, discussing the work of Sacks and Garfinkel to reveal the sequential organization of moral conduct in situ. The children's multimodal ways of embodying chosen destructive characters through predicated actions reveal how they attempt to evade negative consequences of breaking promises through pretend play. The article concludes with connections to moral philosophy, and by discussing how the turns of talk and gesture co-produce complex learning of culturally and morally appropriate behaviours in situ.